Alkyl caffeates improve the antioxidant activity, antitumor property and oxidation stability of edible oil. - Jun Wang; Shuang-Shuang Gu; Na Pang; Fang-Qin Wang; Fei Pang; Hong-Sheng Cui; Xiang-Yang Wu; Fu-An Wu (PLoS ONE)
Caffeic acid (CA) is distributed widely in nature and possesses strong antioxidant activity. However, CA has lower solubility in non-polar media, which limits its application in fat-soluble food. To increase the lipophilicity of natural antioxidant CA, a series of alkyl caffeates were synthesized and their antioxidant and antitumor activities were investigated. The antioxidant parameters, including the induction period, acid value and unsaturated fatty acid content, of the alkyl caffeates in edible oil were firstly investigated. The results indicated that alkyl caffeates had a lower DPPH IC₅₀ (14-23 µM) compared to CA, dibutyl hydroxy toluene (BHT) and Vitamin C (24-51 µM), and significantly inhibited four human cancer cells (SW620, SW480, SGC7901 and HepG2) with inhibition ratio of 71.4-78.0% by a MTT assay. With regard to the induction period and acid value assays, methyl and butyl caffeates had higher abilities than BHT to restrain the oxidation process and improve the stability of edible oil. The addition of ethyl caffeate to oil allowed maintenance of a higher unsaturated fatty acid methyl ester content (68.53%) at high temperatures. Overall, the alkyl caffeats with short chain length (n<5) assessed better oxidative stability than those with long chain length. To date, this is the first report to the correlations among the antioxidant activity, anticancer activity and oxidative stability of alkyl caffeates.